Supplement of 1,25-dihydroxycholecalciferol and reduction of calcium and available phosphorus to female broilers (Research, Society and Development, 2020)
The poultry industry has required effective nutritional programs to obtain the exact supply of nutrients to animals, to reduce costs, and to minimize the environmental impacts arising from excreta from animal production. Among such nutrients, there are vitamins and minerals, essential for animal development, since they participate in numerous physiological processes. The objective of this study was to evaluate the performance and yield of carcass and noble cuts yield of female broilers fed diets supplemented with 1,25-dihydroxycholecalciferol (1,25(OH)2D3) and reduced levels of calcium (Ca) and available phosphorus (Pav). A randomized block design was used, with six treatments (0.0; 1.0; 2.0; 3.0; 4.0 and 5.0 µg of active vitamin D3/kg of diet), and six repetitions with 17 birds each (n=612). The active vitamin D3 studied (1,25(OH)2D3-glycoside) was of herbal origin, derived from Solanum glaucophyllum. The supplementary use up to 5 µg 1,25(OH)2D3/kg of feed associated with suboptimal levels of Ca and Pav, there was a linear decrease in feed consumption (p